Biographieforschung im Diskurs - Völter, Bettina; Dausien, Bettina; Lutz, Helma; Rosenthal, Gabriele (VS, Verl. für Sozialwiss., 2005)
Mit Beiträgen von Ursula Apitzsch, Monika Wohlrab-Sahr, Gehard Jost, Jan Coetzee, Lena Inowlocki, Bettina Völter/Thomas Schäfer, Bettina Dausien/Helga Kelle, Gabriele Rosenthal, Michaela Köttig, Gerhard Riemann, Helma Lutz/Kathy Davis, Peter Alheit, Roswitha Breckner, Ingrid Miethe/Silke Roth, Brian Roberts